Emotional distress tolerance across anxiety disorders. (May 2016) - Michel, Natalie M.; Rowa, Karen; Young, Lisa; McCabe, Randi E.
Highlights: We examine emotional distress tolerance (EDT) across anxiety disorders. We also assess its relationship to symptom severity and impairment. Poor EDT is transdiagnostic but is not uniquely related to symptoms nor impairment. Intolerance of uncertainty (IU) and anxiety sensitivity (AS) are better predictors. IU and AS are more important to target in treating anxiety disorders than EDT. Abstract: Emotional distress tolerance (EDT) has increasingly been recognized as a transdiagnostic vulnerability factor. However, research assessing EDT in anxiety disorder populations is lacking. The current study addressed this gap in the literature by examining EDT in a sample of outpatients with panic, social anxiety, generalized anxiety, or obsessive compulsive disorders ( n = 674), and by assessing its relationship to symptom severity and impairment. Results showed that poor EDT was common across diagnostic groups. However, correlation and regression analyses suggested that although EDT was associated with symptom severity and impairment, it did not account for unique variance in scores beyond the effect of negative affect, stress, intolerance of uncertainty (IU) and anxiety sensitivity (AS). IU and AS had a stronger relationship with overall symptom severity and impairment in the regression models. Together, findings suggest that although EDT may be transdiagnostic, IU and AS are more relevant to our understanding of anxiety disorders.